2010
DOI: 10.1111/j.1439-0426.2010.01506.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and reproduction of introduced goldfish Carassius auratus in small ponds of southeast England with and without native crucian carp Carassius carassius

Abstract: The ornamental Asiatic species, goldfish Carassius auratus, was introduced to open waters of the UK in the late 17th century. The species reproduces readily in small ponds and threatens native species, in particular crucian carp Carassius carassius, but surprisingly there are no known published studies on the growth and reproduction of feral pond populations of this species in the UK and relatively few elsewhere. The aim of the present study was to assess the growth (back-calculated length at age), body condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…This suggests that both species were exploiting similar resources that were sufficiently abundant not to result in depressed growth rates. These results were also in line with those of Tarkan, Cucherousset, Zięba, Godard, & Copp (2010), who suggested that across four invaded wild ponds, there was no difference in the growth rates of C. carassius in C. auratus when compared with ponds where C. auratus was absent. However, when C. carassius was sympatric with C. carpio in the pond experiment, their isotopic niche shifted to a higher trophic position compared with allopatry and their growth rate was significantly depressed (Busst and Britton, 2017).…”
Section: Trophic Niche Partitioning Between Invasive and Native Fishesupporting
confidence: 91%
See 1 more Smart Citation
“…This suggests that both species were exploiting similar resources that were sufficiently abundant not to result in depressed growth rates. These results were also in line with those of Tarkan, Cucherousset, Zięba, Godard, & Copp (2010), who suggested that across four invaded wild ponds, there was no difference in the growth rates of C. carassius in C. auratus when compared with ponds where C. auratus was absent. However, when C. carassius was sympatric with C. carpio in the pond experiment, their isotopic niche shifted to a higher trophic position compared with allopatry and their growth rate was significantly depressed (Busst and Britton, 2017).…”
Section: Trophic Niche Partitioning Between Invasive and Native Fishesupporting
confidence: 91%
“…This means that their results might not scale up to represent those in more complex and stochastic environments (Korsu, Huusko & Muotka, 2009;Spivak, Vanni & Mette, 2011). It has already been outlined that the results of the aquaria tank based experiments involving Carassius fishes were not consistent with those from pond experiments (Busst and Britton, 2017) or patterns observed in the wild (Tarkan et al, 2010). Whilst tank aquaria results still have some utility, their use of fixed food rations means that these are limited resources, with the pond experiment results suggesting that food resources are rarely limiting in more wild contexts.…”
Section: Discussionmentioning
confidence: 96%
“…Non‐native populations have become established in at least 70 countries and are in the list of the ten most invasive aquatic species (Crossman, ; García‐Berthou et al., ). Their ability to colonize waters and develop invasive populations is enhanced by factors including their high environmental tolerances and fractional spawning strategy, with reproduction potentially occurring over several months a year (Tarkan et al., ). Their invasive impacts include increased competition for resources with native fishes (Ford and Beitinger, ; Lorenzoni et al., ) and hybridizing with congeners, leading to local extinctions (Hänfling et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…These divergence time priors were set in order to represent the possible time windows of C. carassius introduction under our three hypotheses. To test hypothesis (1)-the natural colonization of C. carassius more than 7,800 YBP, the time prior for the oldest split between English and Continental European populations was set to 4,000-10,000 generations (equivalent to 8,000-20,000 YBP, assuming a mean generation time of 2 years (Tarkan, Cucherousset, Zięba, Godard, & Copp, 2010;Fig. S1: scenarios 1-6).…”
Section: Testing the Native Status Of Carassius Carassius In Englandmentioning
confidence: 99%